TRAUMATIC MUTISM AS COPING MECHANISM: DISSOCIATIVE BEHAVIOUR OF MAYA IN I KNOW WHY THE CAGED BIRD SINGS - Pearl, Chrisma S.; Dunston, Joseph (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Trauma is a foremost theme of contemporary literature. The term “post-traumatic stress disorder” (PTSD) found its existence in the 1980s, exploring the shattering effects of trauma on the victim. Traumatic mutism is one such psychological disorder characterised by the victim’s sudden inability to speak, following the trauma. The protagonist Maya in I Know Why the Caged Bird Sings, is subjected to the horror of incest at the age of seven. Overwhelmed by the incident, she locks herself in a private cage of self-imposed silence for four long years. Applying Jennifer Freyd’s “Betrayal Trauma Theory”, the article discusses the events that led to Maya’s silence. She is dumbstruck, fearing the repressive consequences of this pathetic predicament in the community. And to wriggle out of the present pathos, the post-traumatic symptoms, such as psychic numbing, withdrawal and mutism are adopted by the victim. The article further presents the importance of external sources that help the victim out of these dissociative behaviours. The article concludes by stating the role of literature both as a therapeutic tool for the victim and as a narrative tool for the readers, providing an accurate understanding of trauma and its implications.